2013
DOI: 10.2169/internalmedicine.52.9047
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Plasma Vitamin D Levels in Patients with Undifferentiated Spondyloarthritis and Ankylosing Spondylitis

Abstract: Objective The aim of the present study was to evaluate the plasma vitamin D (vit D) levels and their association with the disease activity in patients with ankylosing spondylitis (AS) and undifferentiated spondyloarthritis (uSpA) compared with healthy populations. Methods This study included 161 spondyloarthritis patients (113 uSpA patients and 48 AS patients) attending our rheumatology out-patient clinic, along with 92 controls. Results The plasma vit D levels were 18 μg/L (8-38) in the AS group, 20 μg/L (4-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
5
26
4
1
Order By: Relevance
“…However, in the early phases of osteomalacia biochemicals such as calcium, phosphate and soluble phosphatase are released in serum because of a low 25(OH)D level, may be lacking due to compensatory changes conversely the PTH may be lifted and it lead to decalcification of the skeleton . AS patients are associated with low vitamin D in serum concentrations are linked with higher disease activity [15]. Although vitamin D concentrations were not associated with higher disease activity in our study, vitamin D levels were significantly lower in axSpA patients.…”
Section: Discussion:-contrasting
confidence: 71%
“…However, in the early phases of osteomalacia biochemicals such as calcium, phosphate and soluble phosphatase are released in serum because of a low 25(OH)D level, may be lacking due to compensatory changes conversely the PTH may be lifted and it lead to decalcification of the skeleton . AS patients are associated with low vitamin D in serum concentrations are linked with higher disease activity [15]. Although vitamin D concentrations were not associated with higher disease activity in our study, vitamin D levels were significantly lower in axSpA patients.…”
Section: Discussion:-contrasting
confidence: 71%
“…While several studies had shown the aggravating effect of vitamin D's deficiency in the activity markers of AS disease [61][62][63][64] , other studies have not found any correlation [65][66][67] . Although, there is evidence for increased risk of AS in people with deficiency of vitamin D [68][69][70] further studies are required to clarify the causal relationship between the deficiency of vitamin D and activity of AS disease.…”
Section: Vitamin D and Severity Of Asmentioning
confidence: 91%
“…In a study of 48 AS patients has been reported a significant correlation between plasma 25(OH)D levels and erythrocyte sedimentation rate (ESR)/CRP, but did not observe any significant correlation with BASDAI 61 . Hmamouchi et al showed that there is a significant inverse correlation between 25(OH)D and Bath AS Functional Index (BASFI)/BASDAI adjusted to gender and age 62 .…”
Section: Therapeutic Effect Of Vitamin D Supplementation In Asmentioning
confidence: 94%
“…Therefore, factors affecting the immune system may have effects on the disease course. One of these factors affecting the immune system is vitamin D. 2 The relationship between serum vitamin D levels and disease activity scores in patients with AS has been studied in a number of studies [3][4][5] with varying results. Based on this controversy, we aimed to elucidate the relationship between serum vitamin D levels and disease activity scores in AS patients as well as to compare vitamin D levels of AS patients with healthy individuals.…”
mentioning
confidence: 99%
“…There was no significant correlation between vitamin D levels and BASDAI scores (r= -0.035, p=0.765). Although the relationship between serum vitamin D levels and disease activity in AS has been studied in a number of studies, [3][4][5] only one study showed a relationship between 25-OH-D levels and disease activity. 4 Lange et al 5 reported a correlation between disease activity in AS and 1,25-OH-D metabolites levels; however, not with 25-OH-D. We used 25-OH-D which is the major circulating form of vitamin D.…”
mentioning
confidence: 99%